Peran Birokrasi dan Implementasi Kebijakan Pendidikan Islam Dasar dan Menengah Formal Era Orde Baru - Ahmad Ali Riyadi, Khoiriyah, (Ali Muchasan, 2020)
This paper analyzes the implementation of New Order government bureaucracy in relation to elementary and secondary Islamic education policy. The aim is to uncover the extent of the role of government bureaucracy in managing Islamic and primary education institutions. This study method used in this study is by searching literature, both primary and secondary data, with a historical approach. Analysis of this research data with analytical content. The results show that, first, New Order government issued a policy of primary and secondary Islamic education strictly by issuing educational laws and government regulations as well as derived regulations. Secondly, Islamic education institutions at the elementary and secondary levels experience the formalization of government bureaucracy so that Islamic education that does not follow bureaucratic rules is not formally recognized